KAJIAN DAMPAK PROSES PRODUKSI NATURAL GAS TERHADAP LINGKUNGAN PADA SEBUAH PERUSAHAAN MINYAK DAN GAS DENGAN MENGGUNAKAN LIFE CYCLE ASSESSMENT (LCA) - Pritasari, Sintia (Naturalis: Jurnal Penelitian Pengelolaan Sumberdaya Alam dan Lingkungan, 2023)
The process of natural gas production starting from drilling, processing, and distribution has the potential to release harmful substances into the environment. Therefore, it is necessary to analyze and identify the impact of natural gas production using the Life Cycle Assessment (LCA) method. In this study, the environmental impact of natural gas production was identi-fied using a gate-to-gate approach, using LCA and Microsoft Excel methods. The unit of func-tion used is 1 MMSCF (Million Million of Standard Cubic Feet). LCA methods include goal set-ting and scoping, Life Cycle Inventory (LCI), Life Cycle Impact Assessment (LCIA), and data interpretation. Environmental impacts are categorized using the CML-1A baseline, which includes Global Warming Potential, Acidification Potential, Eutrophication Potential, Photo-chemical Oxidation and Human Toxicity. LCA analysis shows that every 1 MMSCF of natural gas production will contribute to Global Warming Potential 4,067.72 kg CO2eq, Acidification Potential 2,07459 kg SO2eq, Eutrophication Potential 0.25365 kg PO4eq, Photochemical Oxi-dation 0.09891 kg C2H4 eq and Human Toxicity 2.41181 kg 1,4-DB eq. In the natural gas production process, the highest environmental impacts identified are from Gas Turbine Gen-erator (GTG) with Global Warming Potential of 1,986.78 kg CO2eq, Acidification Potential of 1.01686 kg SO2eq, Eutrophication Potential 0.11865 kg PO4 eq, Photochemical Oxidation 0.04813 kg C2H4 eq and Human Toxicity 1.13150 kg 1.4-DB eq. GTG converts energy from fuel combustion to generate electricity for production process equipment and office build-ings. High electricity consumption will further increase GTG gas fuel consumption which will contribute to increased Global Warming Potential, Acidification Potential, Eutrophication Potential, Photochemical Oxidation and potential human toxicity environmental impacts.           Keywords : Life cycle assessment (LCA), natural gas, oil and gas company